Phycobilin pigments as building blocks of artificial light-harvesting structures - Malinová, Kateřina (Jihočeská univerzita, 2021)
Phycobilin mixture was extracted from Thermosynechococcus elongatus cyanobacteria and purified with TLC method. Pure phycocyanobilin was esterified by Fischer esterification by several alcohol types. The results were analysed by TLC and HPLC methods.
Phycobilin pigments as building blocks of artificial light-harvesting structures
Keywords: phycobilins; aggregates; HPLC; TLC; esterification; aggregates